Cognitive Distortions in Relation to Plasma Cortisol and Oxytocin Levels in Major Depressive Disorder - Thomas, Susan Jennifer; Larkin, Theresa (Frontiers in Psychiatry, 2020)
Negative thinking is prominent in major depressive disorder (MDD). Cognitive models propose that negative thinking influences the hypothalamus-pituitary-adrenal axis and cortisol release. Oxytocin is also linked to MDD, social and affective processing and stress buffering. Little research has examined direct relationships between negative cognitions, cortisol and oxytocin. Methods: Sixty-one unmedicated participants meeting DSM-5 criteria for MDD and 60 healthy controls completed measures of psychopathology, stress and cognitions. Plasma samples were analysed for cortisol and oxytocin. Between-group and regression analyses were conducted. Results: Depressed participants reported greater frequency and believability of negative thoughts than controls. Cortisol levels were positively, and oxytocin inversely, correlated with negative thinking. Cortisol and negative thinking accounted for unique variance in depression, and the relationship between stress and cortisol depended on the extent of negative cognitions. Conclusions: The results support long-standing cognitive models which propose that negative thoughts are important in the relationship between stress and cortisol levels.